2009
DOI: 10.1021/jp905139n
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Dynamics of the Fluorescent Probe PRODAN in Heterogeneous Environments: Contributions from the Locally Excited and Charge-Transferred States

Abstract: The coexistence of different excited states with different properties of the same chromophores could have significant consequences for the accurate characterization of solvation dynamics in a heterogeneous environment, such as a protein. The purpose of this work is to study the contributions of the locally excited (LE) and charge-transferred (CT) states of the fluorescent probe molecule 6-propionyl-2-(N,Ndimethylamino)naphthalene (PRODAN) to its solvation dynamics in the heterogeneous environment provided by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 72 publications
5
63
0
Order By: Relevance
“…[24,25] Moreover, we have shown the possibility of switching the state from where PRODAN emits by changing the properties of the AOT RM interfaces. [25] Adhikary et al, [40] by solvation dynamics, have found that the LE and ICT states of PRODAN solvate on different timescales in AOT RMs (2 and % 0.4 ns, respectively), consistent with our results. In consequence, the photophysics of PRODAN is very helpful to test the unique RM interface properties.…”
Section: Introductionsupporting
confidence: 92%
“…[24,25] Moreover, we have shown the possibility of switching the state from where PRODAN emits by changing the properties of the AOT RM interfaces. [25] Adhikary et al, [40] by solvation dynamics, have found that the LE and ICT states of PRODAN solvate on different timescales in AOT RMs (2 and % 0.4 ns, respectively), consistent with our results. In consequence, the photophysics of PRODAN is very helpful to test the unique RM interface properties.…”
Section: Introductionsupporting
confidence: 92%
“…81, 82 Briefly, PRODAN® dissolved in methanol was aliquoted into black 96-well plates. After drying overnight, micelle solutions at a range of concentrations (0–2 mg/ml) were added and incubated overnight to achieve final PRODAN® concentrations of 5.45*10 −4 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…15 Because the Stokes shift depends on both polarity and H-bonding, conclusions about micropolarity that are based on the Stokes shift must be considered carefully. 12,16 …”
Section: Introductionmentioning
confidence: 99%